Effects of Eye Movement Desensitization and Reprocessing on disease symptoms and functionality in patients with psychotic disorders - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2019)
It is known that past stressful life events have significant effects on the emotions, thoughts, and behaviors of individuals. Evaluation of the factors that trigger the onset of psychiatric factors revealed that negative life events and traumatic experiences have an effect on individuals. Recognition of the comorbidities of posttraumatic stress disorder (PTSD) with other psychiatric disorders has a critical role in the treatment process. Questioning the history of trauma in individuals who are diagnosed with a psychotic disorder is effective in both increasing the efficiency of drug treatment, reducing the severity of symptoms, and improving the quality of life of the patient. Literature shows that the prevalence of PTSD is significantly higher in schizophrenia patients than in the healthy population. Eye Movement Desensitization and Reprocessing (EMDR) is a psychotherapy method, which is shown to be effective in several mental disorders, particularly PTSD. In literature, there is a limited number of studies about the effectiveness of EMDR therapy in patients diagnosed with psychosis. In this case series, it has been shown that the administration of EMDR therapy reduced the positive and negative symptoms and contributed to the improvement in the functioning of the patients.
Keywords: eye movement desensitization reprocessing (EMDR); psychotic disorders; schizophrenia; traumatic events; CHILDHOOD TRAUMA; STRESS-DISORDER; TURKISH VERSION; SCHIZOPHRENIA; VALIDATION; REMISSION; VALIDITY; EMDR